Transarterial chemoembolization and early arterial complications after liver transplantation for hepatocellular carcinoma - V. V. Borovik; A. A. Polikarpov; D. A. Granov (Вестник трансплантологии и искусственных органов)
Objective: to evaluate the possible influence of neoadjuvant transarterial chemoembolization (TACE) on development of early arterial complications after orthotopic liver transplantation (OLTx). Materials and methods. The work is based on treatment-related data of 250 recipients. The analyzed group included 21 patients with hepatocellular carcinoma (HCC). In all recipients who underwent primary transplantation (n = 228), possible negative factors influencing the development of early arterial complications were analyzed, such as degree of allograft steatosis, cold and warm ischemia time, revascularization duration, blood pressure level after arterial reconstruction, and exchange transfusion volume. Results. The degree of allograft steatosis did not differ between HCC patients and the general sample (95% CI, p = 0.25). No early arterial complications were revealed during TACE. There was no significant difference in preservation parameters, arterial revascularization time, systolic blood pressure level at blood flow start, and exchange transfusion volume (CI 95%, p > 0.05). The incidence of early vascular complications in the study group was 16.7%, it did not differ from the entire sample (95% CI, p = 0.96). Conclusion. The incidence of early arterial complications of OLTx in patients who underwent TACE does not significantly increase both according to the literature and our own findings. When vascular complications of OLTx occur, image-guided endovascular intervention is the method of choice for treatment.